THE STUDY OF THE PHENOMENON OF ABBREVIATION IN UZBEK LINGUISTICS - Dilrabo Shuhratovna Bobomurodova; Jovbo‘riyeva Saodat O‘ktamovna (Western European Studies, 2025)
This article analyzes the role of abbreviations (shortened words) in linguistic research, their morphological characteristics, and methods of formation. In modern linguistics, abbreviations are viewed not only as a means of condensing language and speeding up information exchange, but also as a reflection of cultural and technological changes. The article presents the main types of word shortening – apocopes, acronyms, partial component usage – with examples
Keywords: Abbreviation; apocope; acronyms; alphabetic